Ideology and Taxation in Latin America - Ernesto H. Stein; Lorena Caro (Inter-American Development Bank (IDB), 2013)
This paper examines the impact of ideology on tax revenues in Latin America, using a panel of 17 countries from 1990 to 2010. As a first approach, a fixed- effects model is used to identify the impact of ideology on taxation; left-leaning governments are associated with increases in total tax revenues and income tax revenues of 2. 1 and 1. 3 percent of GDP, respectively. There is no effect on revenues from VAT or social security taxes. To deal with endogeneity problems, an event study and a difference in difference methodology are used to track the behavior of revenues around the time of the shifts to the left. Tax revenues and income tax revenues increase by 1. 5 and 0. 8 percent of GDP when comparing revenues immediately before and after the shift in ideology. The pattern of tax revenues around ideological shifts suggests that the effects are causal.
Keywords: H20; P16; 330